Antioxidant properties of flours of different origins - Miśkiewicz, Karolina; Nebesny, Ewa; Rosicka-Kaczmarek, Justyna; Żyżelewicz, Dorota (Lodz University of Technology Press, 2015)
Plant materials are a rich source of many biologically active compounds that can be applied to food products or intended for direct consumption. Among the plant products Among the plant products with a particularly high antioxidant activity are berries, herbs, spices, grains and legumes. Flour is one of the main raw materials used in both bakery and pastry industry. Flours are rich in biologically active compounds and possess antioxidant properties. According to the literature, botanical origin of raw vegetable materials affects the polyphenol content as well as the antioxidant properties of flours derived from them [1]. The aim of the study was to determine the polyphenol content and antioxidant properties of flours of different origins.